ANTHROPOMORFISM STRATEGY IN BUILDING LEGENDARY COFFEE BRANDS IN BANDUNG CITY - Mutia Tri Satya; Steffani Lule; Abdul Fidayan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Purpose – The purpose of this paper is to develop and empirically test a research model examining the impact of Antropomorpishm strategy to create impact to build brand awareness and bring interest and to increase sales on 5 legend coffee brand in Bandung City. Design – The research model tested for 488 college students who regularly consumes coffee every day. Data were collected in Bandung using a self-administered onoine survey. Data analysis uses partial least swuares-structural equation modelling (PLS-SEM). Findings – The research found that if a brand uses the Anthropomorpism strategy, it can affect humans emotionally and make the brand closer to the user. The results show that the brand will become one with them because the brand has something unique and familiar to show. Research limitation/implication – Through this research, it is hoped that legendary coffee can be used as input so that the product becomes a product that can innovate and be able to compete with other products even though it already has a brand as legendary coffee. Besides, it is also hoped that this research can be a reference source for future research that has similar topics and discussions. in order to be much better. Originality/value – The role of brand awareness is very important for SMEs so that their products are easily being recognize by consumers. The formation of a brand image can be done using anthropomorphism strategies. This paper contributes to the marketing literature by developing and empirically testing a research model Brand awareness, anthropomorphism, and to increase sales to coffee product in Bandung.